Industri Baru Pada Struktur Pasar Industri Pada Kota Malang - Muhammad Yasin; Khosnol Khotimah; Joanne Andre Toy Panga (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
This reasearch aimed to determine the condition of ceramic industry in Malang City and calculate the market structure of ceramic industry in detail by using market structure approach. This approach can be calculated by using market share, Hirchman Herfindahl Index (IHH), and CR4 (Concentration Ratio for Biggest Four). This study used quantitative descriptive analysis with the markets as the object of study. The result of the study showed that the market had the largest concentration ratio with 12.12% that led to the market structure of competition. The value for IHH was 0.05 that led to the perfect competition market because its value was between zero and one. Then, the value of CR4 was 0.36 that led to perfect competition market structure because its value was < 20%. It can be concluded that the degree of ceramic industry business in Malang City went to perfect competition market structure.